THE EFFECTIVENESS OF QAR STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION - Apriyani, Sri Devi; Aminah, Aminah; Mukrim, Mukrim (e-Journal of ELTS (English Language Teaching Society), 2024)
The purpose of this research is to prove that the Question-Answer Relationship (QAR) strategy is effective in improving reading comprehension of grade VIII students of SMP Negeri 3 Mepanga and to find out whether there was a significant difference between the experimental class and the control class in reading comprehension. The design of this research was quasi-experimental. The samples of this research consisted of 45 students who were selected by using cluster random sampling. The research instrument used to collect the data was a multiple-choice test which were divided into pre-test and post-test. The data were analyzed by using statistical analysis. The result of the data analysis shows that there was a significant effect on students’ reading comprehension after the treatment by applying the QAR strategy. It indicated the mean score of both test results where the mean score of the experimental class significantly improved from 38.75 to 63.75. Meanwhile, the mean score of the control class is from 30.00 to 40.00. Based on the result of the data analysis, the researcher found that the value of t-counted is 7.36. By applying a degree of freedom (df) 43 (24 + 21 – 2) and 0.05 level of significance, the researchers found that the value of the t-table is 1.68. It means that the hypothesis is accepted because the value of t-counted (7.36) is higher than the t-table (1.68). To conclude, the QAR strategy is effective in improving reading comprehension of grade VIII students of SMP Negeri 3 Mepanga.